Mental and Spiritual Impacts of Children Victims of The 2018 Earthquake in Lompio Village, Sirenja District, Donggala Regency - Fatimah Saguni; Zahir Zahir; Rusdin Rusdin (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2022)
This study discusses the mental and spiritual impact of children victims of the 2018 earthquake victims in Lompio, Sirenja District, Donggala Regency. The objectives of this study are to know the Mental Spiritual form of the 2018 Earthquake victim children and mental spiritual recovery strategies for victim children. This study also discusses the supporting and inhibiting factors in the mental spiritual recovery of the victim children in the area. This f research used a case study approach. The study showed that the children experienced negative feeling due to trauma caused by the earth quake catasthrophy. Such negative feelings invluded fear, anxiety, fear of praying at the mosque, and lack of interest to continue farmingl. However, there was also a positive impact of the catastrhophy becuase the children become more religius by practicing islamic teaching regularly such as praying and helping fellow friends. For mental strategy recovery, the local government implemented Al-hikmah method with a divine approach and the al-mauidzatil hasanah method. More actors were involved in the recovery program such as local government officials, village government, NGOs, formal education teachers, Islamic religious teachers, parents, and other community-related parties.